2018
DOI: 10.1016/j.jvs.2017.11.082
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative mapping of the aortoiliac territory with duplex ultrasound in patients with peripheral arterial occlusive disease

Abstract: DUS mapping of the aortoiliac territory could be used as a single preoperative imaging test in aortoiliac occlusive disease in patients whose DUS examination is able to be evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…However, it should be noted that this sensitivity could be lower for the aorto‐iliac trajectory because of obesity or over‐projection of bowel gas. A study found that 10.4% of all duplex images of the aorto‐iliac trajectory could not be evaluated because of these reasons [ 36 ]. Another study found a low inter‐observer agreement for duplex ultrasound in the case of the aorto‐iliac trajectory (kappa of 0.53) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that this sensitivity could be lower for the aorto‐iliac trajectory because of obesity or over‐projection of bowel gas. A study found that 10.4% of all duplex images of the aorto‐iliac trajectory could not be evaluated because of these reasons [ 36 ]. Another study found a low inter‐observer agreement for duplex ultrasound in the case of the aorto‐iliac trajectory (kappa of 0.53) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to CT, DUS had low accuracy reports, with cases ranging from 5.6 mm smaller to 11.6 mm bigger than the reported diameter on CT [23]. Moreover, DUS underestimates the degree of stenosis compared to CTA (degree of concordance has been reported in more studies [5,24] between DUS and CTA: common iliac: 0.8 (0.71-0.88), right external iliac: 0.84 (0.76-0.92), left external iliac: 0.71 (0.61-0.81)) or MRA (degree of concordance between DUS and MRA: 86%). DUS provides a moderate to strong correlation with MRI [12].…”
Section: Diagnostic Methodsmentioning
confidence: 97%
“…In native arteries, DUS had a PSV = 180 cm/s, 80% specificity, and 66% sensitivity for >50% stenosis [ 20 ]. There is a strong degree of concordance between DUS and CTA in the right femoral (0.82 [0.69-0.95]) and left femoral (0.88 [0.76-1]) arteries [ 24 ]. In the femoropopliteal segments, DUS provided 94.8% sensitivity, 80.2% specificity, 94.1% PPV, 89.0% NPV, and 90.1% accuracy [ 25 ].…”
Section: Reviewmentioning
confidence: 99%